2007
DOI: 10.1021/ja077288d
|View full text |Cite
|
Sign up to set email alerts
|

Mimicry of Antimicrobial Host-Defense Peptides by Random Copolymers

Abstract: Efforts to generate antibacterial agents via mimicry of host-defense peptides have focused on discrete oligomers that can adopt a regular globally amphiphilic conformation in the presence of bacterial cell membranes and ultimately disrupt those membranes. Although considerable success has been achieved with this approach, application of the resulting molecules is hampered by the high cost associated with stepwise oligomer synthesis. We show that random poly-β-peptide copolymers, prepared by ring-opening polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
452
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(465 citation statements)
references
References 31 publications
11
452
2
Order By: Relevance
“…The globally amphiphilic conformation could perform the key roles for considerable antimicrobial activity, as shown in Figure 5. 64 It is found that higher ratio of cationic groups can benefit to reduce the hemolytic effect, while higher ratio of hydrophobic groups is of great importance for antimicrobials. They utilized minimum hemolytic concentration to display biocompatibility of antimicrobial cationic polymers.…”
Section: Induced Globally Amphiphilic Conformationmentioning
confidence: 99%
“…The globally amphiphilic conformation could perform the key roles for considerable antimicrobial activity, as shown in Figure 5. 64 It is found that higher ratio of cationic groups can benefit to reduce the hemolytic effect, while higher ratio of hydrophobic groups is of great importance for antimicrobials. They utilized minimum hemolytic concentration to display biocompatibility of antimicrobial cationic polymers.…”
Section: Induced Globally Amphiphilic Conformationmentioning
confidence: 99%
“…Upon binding to membranes, they often organize as α-helices with hydrophobic and hydrophilic residues on opposite faces, a feature referred to as secondary amphipathic character. Designers of synthetic CAPs found that it was possible to modify CAP activity towards microbial and mammalian cells independently by varying the hydrophobicity, as well as the number and the position of the positive charges in the amphiphilic structure [3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Melittin-21Q exhibited a reduced or similar binding to DMPC and to DMPG bilayers compared to native melittin, suggesting a favorable or a limited contribution of the cationic C-terminal portion to membrane affinity. Another investigation, using tryptophan fluorescence, revealed that melittin and its Cterminal truncated versions , and [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], all showed an increased affinity for 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC)/1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-(1'-rac-glycerol) (POPG) 70/30 large unilamellar vesicles (LUVs) compared POPC LUVs 47 (See Supporting Information). These findings highlighted the role of attractive electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been growing interest in synthetic polymer-based AMP mimics bearing both cationic and hydrophobic groups, which can be prepared through cost-effective polymerization processes. For example, simplified polymeric AMP analogs have been developed, including poly (methacrylamides) (31), poly(β-lactams) (14,(32)(33)(34)(35), polypeptides (36)(37)(38), poly(norborenes) (39,40), and poly(carbonates) (41,42). These compounds are considerably less expensive than peptides, and much work is being done to optimize them.…”
mentioning
confidence: 99%